9(s+7)-(7s+m)-9m=

Simple and best practice solution for 9(s+7)-(7s+m)-9m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(s+7)-(7s+m)-9m= equation:


Simplifying
9(s + 7) + -1(7s + m) + -9m = 0

Reorder the terms:
9(7 + s) + -1(7s + m) + -9m = 0
(7 * 9 + s * 9) + -1(7s + m) + -9m = 0
(63 + 9s) + -1(7s + m) + -9m = 0

Reorder the terms:
63 + 9s + -1(m + 7s) + -9m = 0
63 + 9s + (m * -1 + 7s * -1) + -9m = 0
63 + 9s + (-1m + -7s) + -9m = 0

Reorder the terms:
63 + -1m + -9m + 9s + -7s = 0

Combine like terms: -1m + -9m = -10m
63 + -10m + 9s + -7s = 0

Combine like terms: 9s + -7s = 2s
63 + -10m + 2s = 0

Solving
63 + -10m + 2s = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-63' to each side of the equation.
63 + -10m + -63 + 2s = 0 + -63

Reorder the terms:
63 + -63 + -10m + 2s = 0 + -63

Combine like terms: 63 + -63 = 0
0 + -10m + 2s = 0 + -63
-10m + 2s = 0 + -63

Combine like terms: 0 + -63 = -63
-10m + 2s = -63

Add '-2s' to each side of the equation.
-10m + 2s + -2s = -63 + -2s

Combine like terms: 2s + -2s = 0
-10m + 0 = -63 + -2s
-10m = -63 + -2s

Divide each side by '-10'.
m = 6.3 + 0.2s

Simplifying
m = 6.3 + 0.2s

See similar equations:

| f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= | | 7x+9=-11x+12 | | 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= | | 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= |

Equations solver categories